Wear-resistant coating with good binding force on surface of aluminum alloy and preparation method of wear-resistant coating
Through the treatment of aluminum alloy SIC sandpaper, ultrasonic cleaning, TI membrane deposition, and arc -light discharge plasma nitrogen seepage treatment, combined with heat treatment, the problem of low surface hardness and abrasion resistance of aluminum alloy, which achieves the improvement of the surface hardness and the decrease in friction coefficients. The effect of enhanced the combination, and the process of energy saving and environmental protection.
Patent Information
- Application Number
- CN202411491051.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The surface hardness of aluminum alloys is low and the wear resistance is poor, which leads to easy corrosion and wear. The existing surface modification technology has problems such as thermal deformation, overburning, difficulty in forming a seepage expansion layer and "eggshell effect".
The pre -processing steps of ultrasonic cleaning are polished with SIC sandpaper, and then the TI film is deposited in the arc ion plating furnace, and the arc -light discharge plasma nitrogen seepage treatment is performed under the 400 ° C vacuum to improve the mechanical performance of the matrix in thermal treatment.
The surface thickness of the aluminum alloy is controllable, the hardness is increased, the friction coefficient is reduced, and the bonding force is enhanced. The wear resistance and anti-corrosion properties of the aluminum alloy are significantly improved, and the process is energy-saving and environmentally friendly.
Smart Images

Figure CN119351953A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a wear-resistant coating with good bonding force on the surface of an aluminum alloy and a preparation method thereof. Background Art
[0002] Aluminum alloy has the advantages of low specific gravity, high specific strength, excellent comprehensive performance and abundant reserves. It is a representative of light alloys and plays an important role in the lightweighting of weapons and equipment. However, due to its low hardness, thin and brittle natural oxide film on the surface, aluminum alloy has problems such as poor wear resistance and easy corrosion, which makes aluminum alloy equipment parts prone to failure. Especially for iron workpieces, due to the large mutual solubility between aluminum and iron, once friction and wear occur, the aluminum element is easy to transfer to the iron parts during the friction process. In the context of modern military applications, the rapid development of aircraft, armored vehicles, ships and submarines has put forward higher requirements on the comprehensive performance of aluminum alloys.
[0003] Due to the diversity and complexity of the service conditions of weapons and equipment, the requirements for the performance of aluminum alloys are often very different. It is difficult to develop new alloy systems for different performance requirements in the short term, and the cost is high. The preparation of high-performance protective coatings on the surface of light alloys through surface engineering technology can not only improve the comprehensive performance of weapons and equipment, but also greatly save costs.
[0004] At present, the commonly used surface modification technologies for improving wear resistance are thermal spraying technology, laser cladding technology, plasma nitriding technology and arc ion plating technology. Among these surface modification technologies, thermal spraying and laser cladding are often accompanied by huge heat in the coating preparation process, which causes certain thermal deformation of the substrate and is difficult to be applied to precision parts. Plasma nitriding is widely used in the steel field, but because the solid solution temperature of aluminum alloy is generally lower than 550℃, aluminum alloy is very likely to be "overburned" at high temperature, which limits the nitriding temperature and is often lower than the formation temperature of AlN. The low solid solubility of nitrogen atoms in the α-Al lattice makes it very difficult for nitrogen atoms to diffuse from the surface to the inside, and it is impossible to form a diffusion layer; in addition, the natural oxide film on the surface of aluminum alloy is very stable and difficult to be completely removed by grinding and polishing, which seriously hinders the diffusion of nitrogen atoms into the matrix. Arc ion plating technology can deposit a nitride hard film on the surface of aluminum alloy to improve the surface hardness and wear resistance. However, due to the huge performance difference between the hard coating and the aluminum alloy, the substrate bearing capacity is insufficient, resulting in the "eggshell effect". The bonding force between the coating and the substrate is low, and the coating is prone to peeling. For example, in “Corrosion protection of magnetron sputtered TiN coatings deposited on high strength aluminium alloys” (Diesselberg M, Stock HR, Mayr P.Corrosion protection of magnetron sputtered TiN coatings deposited on high strengthaluminium alloys[J].Surface&Coatings Technology.2004,177(none)), TiN coating was directly deposited on the surface of aluminium alloy by magnetron sputtering. Obvious cracks were observed at the interface between the coating and the substrate, and the film-substrate bonding was poor. Chinese invention patent CN201511019701.0 used magnetron sputtering composite ion nitriding technology to modify the surface of aluminium alloy, and its surface hardness reached up to 439Hv, which effectively improved the surface hardness and wear resistance of aluminium alloy. However, the composite process takes a long time and consumes a lot of energy, which does not meet the requirements of energy conservation and emission reduction. In addition, the influence of heat treatment on aluminium alloy substrate has also attracted attention. Therefore, it is the direction of efforts of materials workers to explore a method to make the aluminium alloy modified layer bond well with the substrate, increase the surface hardness, improve the friction and wear performance, and minimize the impact on the substrate.
[0005] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of low hardness and poor wear resistance of the existing aluminum alloy surface, and to provide a wear-resistant coating with good bonding force on the aluminum alloy surface and a preparation method thereof.
[0007] In order to achieve the above object, the present invention discloses a method for preparing a wear-resistant coating with good bonding force on the surface of an aluminum alloy, comprising the following steps:
[0008] S1, grinding the aluminum alloy with SiC sandpaper, then ultrasonically cleaning it in anhydrous ethanol for 15 to 30 minutes, taking it out and polishing it, then ultrasonically cleaning it in anhydrous ethanol for 15 to 30 minutes, taking it out and drying it, to obtain a pretreated aluminum alloy;
[0009] S2, placing the pretreated aluminum alloy in an arc ion plating furnace, evacuating, introducing argon gas after heating, glow cleaning the surface of the pretreated aluminum alloy, and then etching the surface of the aluminum alloy. After etching, the arc column current is turned off, the coating program is run, the Ti target is turned on, and the aluminum alloy coated with a Ti film is obtained after deposition;
[0010] S3, after the coating process in step S2 is completed, the temperature of the vacuum chamber is set to 400° C., and after the vacuum chamber is cooled to 400° C., the nitriding process is started, and nitrogen-containing gas is introduced. After the nitriding process is completed, the furnace is cooled to room temperature to complete the preparation of the wear-resistant coating on the surface of the aluminum alloy;
[0011] S4, after the nitriding process in step S3 is completed, the sample is taken out of the furnace, and the aluminum alloy with the coating on the surface is placed in a muffle furnace, and the temperature of the muffle furnace is set to 440°C. After keeping warm for 1 hour, it is taken out and air-cooled. Thereafter, it is placed in an air furnace, and the temperature of the air furnace is set to 110°C. After keeping warm for 8 to 12 hours, it is taken out and air-cooled, thereby completing the preparation of the wear-resistant coating with good adhesion on the surface of the aluminum alloy.
[0012] In the step S1, the mesh number of the SiC sandpaper is 400-2000#.
[0013] In step S2, the specific conditions for glow cleaning are: the vacuum degree of the furnace chamber of the arc ion plating furnace is 5×10 -4 mbar, the vacuum chamber temperature was 420℃, the rotation speed was 3r / min, the amount of argon introduced was 300sccm, the substrate bias was -400V, and the pretreated aluminum alloy surface was glow cleaned for 10min.
[0014] In step S2, the specific etching conditions are: the column arc current is 80A, the substrate bias is -30V, which is gradually adjusted to -180V, and the aluminum alloy surface is etched for 10 minutes.
[0015] In step S2, the specific coating conditions are as follows: the substrate bias voltage is -30 V, which is gradually adjusted to -180 V, the Ti target current is 110 A to 130 A, and the vacuum degree in the arc ion plating furnace is maintained at 2.5×10 -2 mbar, and deposited for 2.5 to 4.5 hours under the conditions of substrate bias -80 V and Ti target current 110A to 130A.
[0016] In step S3, the amount of nitrogen-containing gas introduced is 300 sccm, including 50 sccm nitrogen and 250 sccm argon, and the vacuum degree in the arc ion plating furnace chamber is 3.0×10 -2 mbar, the substrate bias voltage was -30 V, which was gradually adjusted to -300 V, the column arc current was set to 110 A, and then the temperature was 400 °C and the vacuum degree was 3.0 × 10 -2 mbar, substrate bias voltage of -300 V, and column arc current of 110 A for 2 h.
[0017] The invention also discloses a wear-resistant coating with good bonding force on the surface of the aluminum alloy which is prepared by the preparation method.
[0018] The wear-resistant coating has a thickness of 2 μm to 4.3 μm, a hardness of up to 460.8 HV, a friction coefficient of 0.49 to 0.55, and a bonding force of HF3.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] 1. The present invention can obtain a coating with controllable thickness and high hardness on the surface of the aluminum alloy, has good bonding strength with the aluminum alloy substrate, and can achieve the effect of reducing the wear rate;
[0021] 2. The arc discharge plasma nitriding process of the present invention is carried out at a relatively low temperature (400° C.), which meets the requirements of energy saving;
[0022] 3. The aluminum alloy surface strengthening layer prepared by the present invention has a gradient structure, and the outer layer is TiN 0.3 The main phase is titanium-nitrogen solid solution, and the inner layer is an intermetallic compound layer composed of aluminum-based intermetallic compounds;
[0023] 4. In the present invention, coating and nitriding are carried out in the same furnace, which reduces the complexity of the process, improves the efficiency, and achieves the purpose of energy saving;
[0024] 5. The coating obtained after the surface plating treatment of the aluminum alloy of the present invention has high hardness and low friction coefficient, which can effectively improve the use of the treated aluminum alloy in low-speed and light-load transmission occasions. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1X-ray diffraction patterns of untreated aluminum alloy, aluminum alloy with wear-resistant coating on the surface prepared in Example 1, Example 4 and Example 10;
[0026] Figure 2 The cross-sectional microstructure of the aluminum alloy with a wear-resistant coating on the surface prepared in Example 1;
[0027] Figure 3 This is a Rockwell indentation test diagram of the aluminum alloy with a wear-resistant coating on the surface prepared in Example 1;
[0028] Figure 4 1 is a friction and wear performance test curve diagram, 1 is an untreated aluminum alloy, 2 is an aluminum alloy with a wear-resistant coating on the surface prepared in Example 1;
[0029] Figure 5 This is a wear rate diagram of the aluminum alloy with a wear-resistant coating having good surface adhesion prepared in Example 1 after tribological testing. DETAILED DESCRIPTION
[0030] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0031] Example 1
[0032] A method for preparing a wear-resistant coating with good bonding strength on an aluminum alloy surface is specifically carried out according to the following steps:
[0033] 1. Surface pretreatment of aluminum alloy: polish the aluminum alloy with 400-2000# SiC sandpaper, then ultrasonically clean it in anhydrous ethanol for 15-30 minutes, take it out and polish it with diamond grinding paste, then ultrasonically clean it in anhydrous ethanol for 15-30 minutes, take it out and blow dry it to obtain the pretreated aluminum alloy;
[0034] The aluminum alloy is 7075 aluminum alloy;
[0035] 2. Pre-plating pure Ti film on aluminum alloy surface: Place the pre-treated aluminum alloy in the arc ion plating furnace, and adjust the three-dimensional planetary rotating frame to enable the pre-treated aluminum alloy to achieve three-dimensional rotation. Evacuate the arc ion plating furnace chamber to less than 5×10 -4mbar, the vacuum chamber was heated to 420 °C, the rotation speed was set to 3 r / min, and then 300 sccm of argon was introduced, the substrate bias was set to -400 V, and the pretreated aluminum alloy surface was glow cleaned for 10 min. Then the column arc current was set to 80 A, the substrate bias was set to -30 V, and gradually adjusted to -180 V, and the aluminum alloy surface was etched and maintained for 10 min. Then the column arc current was turned off, the coating program was run, the substrate bias was set to -30 V, and gradually adjusted to -180 V. The Ti target current was set to 130 A, and the vacuum degree in the arc ion plating furnace was maintained at 2.5×10 -2 mbar, deposited for 4.5 h under the conditions of substrate bias voltage -80 V and Ti target current 130 A to obtain an aluminum alloy coated with Ti film;
[0036] 3. Arc discharge plasma nitriding in the same furnace: After the coating process is completed, the vacuum chamber temperature is set to 400°C. After the vacuum chamber is cooled to 400°C, the nitriding process is started, and 300sccm of nitrogen-containing gas (50sccm nitrogen, 250sccm argon) is introduced to maintain the vacuum degree in the arc ion plating furnace chamber at 3.0×10 -2 mbar, set the substrate bias voltage to -30 V, gradually adjust to -300 V, set the column arc current to 110 A, and then set the temperature to 400 °C and the vacuum degree to 3.0 × 10 -2 mbar, substrate bias voltage of -300 V, arc current of 110 A, and heat preservation for 2 h. After the program is completed, the aluminum alloy surface is cooled to room temperature with the furnace, and the preparation of the wear-resistant coating is completed;
[0037] 4. Heat treatment to restore the mechanical properties of the matrix aluminum alloy: After the nitriding process is completed and the sample is taken out of the furnace, the aluminum alloy with the coating on the surface is placed in a muffle furnace, and the temperature of the muffle furnace is set to 440°C. After keeping warm for 1 hour, it is taken out and air-cooled. Thereafter, it is placed in an air furnace, and the temperature of the air furnace is set to 110°C. After keeping warm for 12 hours, it is taken out and air-cooled to obtain a coated aluminum alloy with the mechanical properties of the matrix restored. This completes the method for preparing a wear-resistant coating with good adhesion on the surface of the aluminum alloy.
[0038] In this embodiment, arc discharge plasma is obtained by setting the column arc current to 110A.
[0039] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 4.3 μm, a hardness of up to 460.8 HV, a friction coefficient of 0.49, a bonding force of HF3, and a wear rate of 4.03×10 -13 m 3 ·N -1 ·m -1 .
[0040] Example 2
[0041] The difference between this embodiment 1 and embodiment 1 is that the nitrogen flow rate in the nitrogen-containing gas is 100 sccm, and the argon flow rate is 200 sccm, and the rest is the same as embodiment 1.
[0042] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 4.3 μm, a hardness of up to 401.2 HV, a bonding strength of HF3, and a wear rate of 5.29×10 -13 m 3 ·N -1 ·m -1 .
[0043] Example 3
[0044] The difference between this embodiment and embodiment 1 is that in step 2, the Ti target current is adjusted to 110A and the substrate bias is -80V, and then the conditions of the Ti target current of 110A and the substrate bias of -80V are maintained for 2.5 hours. The rest is the same as embodiment 1.
[0045] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 2.1 μm, a hardness of up to 234.1 HV, a bonding strength of HF3, and a wear rate of 12.74×10 -13 m 3 ·N -1 ·m -1 .
[0046] Example 4
[0047] The difference between this embodiment and embodiment 1 is that in step 2, the Ti target current is adjusted to 130A and the substrate bias is -80V, and then the conditions of the Ti target current of 130A and the substrate bias of -80V are maintained for 2.5 hours. The rest is the same as embodiment 1.
[0048] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 2.2 μm, a hardness of up to 251.1 HV, a bonding strength of HF3, and a wear rate of 12.14×10 -13 m 3 ·N -1 ·m -1 .
[0049] Example 5
[0050] The difference between this embodiment and embodiment 1 is that in step 2, the Ti target current is adjusted to 110A and the substrate bias is -80V, and then the conditions of the Ti target current of 110A and the substrate bias of -80V are maintained for 3.5 hours. The rest is the same as embodiment 1.
[0051] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 3.1 μm, a hardness of up to 325.5 HV, a bonding strength of HF3, and a wear rate of 7.11×10 -13 m 3 ·N -1 ·m -1 .
[0052] Example 6
[0053] The difference between this embodiment and embodiment 1 is that in step 2, the Ti target current is adjusted to 130A and the substrate bias is -80V, and then the conditions of the Ti target current of 130A and the substrate bias of -80V are maintained for 3.5 hours. The rest is the same as embodiment 1.
[0054] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 3.3 μm, a hardness of up to 348.1 HV, a bonding force of HF3, and a wear rate of 6.82×10 -13 m 3 ·N -1 ·m -1 .
[0055] Example 7
[0056] The difference between this embodiment and embodiment 1 is that in step 2, the Ti target current is adjusted to 110A and the substrate bias is -80V, and then the conditions of the Ti target current of 110A and the substrate bias of -80V are maintained for 4.5 hours. The rest is the same as embodiment 1.
[0057] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 4.1 μm, a hardness of up to 448.8 HV, a bonding force of HF3, and a wear rate of 4.33×10 -13 m 3 ·N -1 ·m -1 .
[0058] Example 8
[0059] The difference between this embodiment and embodiment 1 is that in step 4, the temperature of the air furnace is set to 110° C., and the furnace is taken out and air-cooled after being kept warm for 8 hours. The rest is the same as embodiment 1.
[0060] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 4.3 μm, a hardness of up to 436.8 HV, a bonding strength of HF3, and a wear rate of 4.74×10 -13 m 3 ·N -1 ·m -1 .
[0061] Example 9
[0062] The difference between this embodiment and embodiment 2 is that: in step 2, the Ti target current is adjusted to 110A and the substrate bias is -80V, and then maintained for 4.5 hours under the conditions of the Ti target current of 110A and the substrate bias of -80V, and in step 4, the air furnace temperature is set to 110°C, and after keeping warm for 8 hours, it is taken out and air-cooled, and the rest is the same as embodiment 1.
[0063] In this embodiment, the wear-resistant coating obtained on the aluminum alloy surface has a thickness of 4.1 μm, a hardness of up to 417.8 HV, a bonding strength of HF3, and a wear rate of 5.03×10 -13 m 3 ·N -1 ·m -1 .
[0064] Figure 1 X-ray diffraction patterns of aluminum alloys with wear-resistant coatings having good adhesion on the surface prepared in Examples 1, 4 and 6; it can be seen from the figure that the coating contains a titanium nitrogen solid solution phase and an aluminum-based intermetallic compound phase.
[0065] Figure 2 The cross-sectional microstructure of the aluminum alloy with the wear-resistant coating having good surface bonding prepared in Example 1; as can be seen from the figure, the coating has good interface bonding with the substrate.
[0066] Figure 3 This is a Rockwell indentation test diagram of the aluminum alloy with a wear-resistant coating having good surface bonding strength prepared in Example 1; the test conditions: using a Rockwell hardness tester, the load is 150g. From the Rockwell indentation diagram obtained by the test, it can be seen that the bonding strength between the coating and the substrate reaches HF3.
[0067] The aluminum alloy with a wear-resistant coating having good bonding strength on the surface prepared in Example 1 and the aluminum alloy not treated by the present embodiment were subjected to friction and wear performance tests; the test conditions were: on a ball-disc friction and wear tester (BRUKER UMTTriboLab), the test disc was a 7075 aluminum alloy sample strengthened by the present embodiment The test ball for the paired grinding is made of GCr15 steel and has a diameter of 6.35 mm. The test is carried out under dry friction conditions with a load of 2 N, a turntable speed of 144 r / min, and a test time of 1000 s.
[0068] Figure 4The friction coefficient curve obtained from the friction and wear performance test, 1 is an untreated aluminum alloy, and 2 is an aluminum alloy with a wear-resistant coating having good bonding strength on the surface prepared in Example 10. As can be seen from the figure, the friction coefficient of the aluminum alloy treated in Example 1 gradually increases with the extension of the wear time. After the wear time is extended to 400s, the friction coefficient tends to be stable, and the average friction coefficient is about 0.49, which is lower than that of the untreated aluminum alloy substrate.
[0069] Figure 5 This is a wear rate diagram of the aluminum alloy having a wear-resistant coating with good adhesion on the surface prepared in Example 1 after tribological testing; as can be seen from the figure, the wear rate of the aluminum alloy treated in Example 1 is significantly lower than that of the untreated aluminum alloy substrate.
[0070] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a wear-resistant coating with good bonding strength on an aluminum alloy surface, characterized in that: The following steps are involved: S1, grinding the aluminum alloy with SiC sandpaper, then ultrasonically cleaning it in anhydrous ethanol for 15 to 30 minutes, taking it out and polishing it, then ultrasonically cleaning it in anhydrous ethanol for 15 to 30 minutes, taking it out and drying it, to obtain a pretreated aluminum alloy; S2, placing the pretreated aluminum alloy in an arc ion plating furnace, evacuating, introducing argon gas after heating, glow cleaning the surface of the pretreated aluminum alloy, and then etching the surface of the aluminum alloy. After etching, the arc column current is turned off, the coating program is run, the Ti target is turned on, and the aluminum alloy coated with a Ti film is obtained after deposition; S3, after the coating process in step S2 is completed, the temperature of the vacuum chamber is set to 400° C., and after the vacuum chamber is cooled to 400° C., the nitriding process is started, and nitrogen-containing gas is introduced. After the nitriding process is completed, the furnace is cooled to room temperature to complete the preparation of the wear-resistant coating on the surface of the aluminum alloy; S4, after the nitriding process in step S3 is completed, the sample is taken out of the furnace, and the aluminum alloy with the coating on the surface is placed in a muffle furnace, and the temperature of the muffle furnace is set to 440°C. After keeping warm for 1 hour, it is taken out and air-cooled. Thereafter, it is placed in an air furnace, and the temperature of the air furnace is set to 110°C. After keeping warm for 8 to 12 hours, it is taken out and air-cooled, thereby completing the preparation of the wear-resistant coating with good adhesion on the surface of the aluminum alloy.
2. The method for preparing a wear-resistant coating having good bonding strength on the surface of an aluminum alloy as claimed in claim 1, characterized in that: In the step S1, the mesh number of the SiC sandpaper is 400-2000#.
3. The method for preparing a wear-resistant coating having good bonding strength on an aluminum alloy surface as claimed in claim 1, characterized in that: In step S2, the specific conditions for glow cleaning are: the vacuum degree of the furnace chamber of the arc ion plating furnace is 5×10 -4 mbar, the vacuum chamber temperature was 420℃, the rotation speed was 3r / min, the amount of argon introduced was 300sccm, the substrate bias was -400V, and the pretreated aluminum alloy surface was glow cleaned for 10min.
4. The method for preparing a wear-resistant coating having good bonding strength on an aluminum alloy surface as claimed in claim 1, characterized in that: In step S2, the specific etching conditions are: the column arc current is 80A, the substrate bias is -30V, which is gradually adjusted to -180V, and the aluminum alloy surface is etched for 10 minutes.
5. The method for preparing a wear-resistant coating having good bonding strength on an aluminum alloy surface as claimed in claim 1, characterized in that: In step S2, the specific coating conditions are as follows: the substrate bias voltage is -30 V, which is gradually adjusted to -180 V, the Ti target current is 110 A to 130 A, and the vacuum degree in the arc ion plating furnace is maintained at 2.5×10 -2 mbar, and deposited for 2.5 to 4.5 hours under the conditions of substrate bias -80 V and Ti target current 110A to 130A.
6. The method for preparing a wear-resistant coating having good bonding strength on an aluminum alloy surface as claimed in claim 1, characterized in that: In step S3, the amount of nitrogen-containing gas introduced is 300 sccm, including 50 sccm nitrogen and 250 sccm argon, and the vacuum degree in the arc ion plating furnace chamber is 3.0×10 -2 mbar, the substrate bias voltage was -30 V, which was gradually adjusted to -300 V, the column arc current was set to 110 A, and then the temperature was 400 °C and the vacuum degree was 3.0 × 10 -2 mbar, substrate bias voltage of -300 V, and column arc current of 110 A for 2 h.
7. A wear-resistant coating having good bonding strength on the surface of an aluminum alloy, which is prepared by the preparation method according to any one of claims 1 to 6.
8. The method for preparing a wear-resistant coating having good bonding strength on an aluminum alloy surface as claimed in claim 7, characterized in that: The wear-resistant coating has a thickness of 2 μm to 4.3 μm, a hardness of up to 460.8 HV, a friction coefficient of 0.49 to 0.55, and a bonding force of HF3.
Citation Information
Patent Citations
Method for enhancing diffusion of plasma on aluminum alloy surface
CN105568211A
TiN coating surface modified titanium alloy bipolar plate and liquid ion nitriding method thereof
CN112467161A
Neodymium-iron-boron magnet composite coating and preparation method thereof
CN116356314A
Aluminum alloy for anodic oxidation tool as well as preparation method and application of aluminum alloy
CN118814029A
Component useful as a cylinder crank housing of an internal combustion engine, comprises a wear resistant-layer, which is formed through an iron alloy coating having pores and net-like channel structures
DE102010049840A1